Daya Hambat Hand Sanitizer di Masyarakat: Apakah Efektif ? - Taslim, Tuty; Salim, Reny; Dewi, Irene Puspa (Jurnal Riset Kefarmasian Indonesia, 2022)
Hand sanitizer is one of the Household Health Supplies (PKRT) which is one of the human needs when the Covid-19 pandemic appears throughout the world. Panic at the beginning of the spread of Covid-19 has caused many people to buy and store hand sanitizers, resulting in shortages everywhere. WHO announced the composition for the manufacture of hand sanitizers. And the government allows making hand sanitizers without going through actual regulations so that hand sanitizers appear in several dosage forms such as sprays and gels suitable for antiseptic purposes. The inhibition of hand sanitizers against microbes needs to be tested considering its function as a microbial exterminator on human hands, so this research needs to be done to determine the effectiveness of hand sanitizers circulating in the community. The microbes used are Staphylococcus aureus and Escherichia coli. The sampling technique was carried out by purposive sampling and its effectiveness by using the disc diffusion method. The results obtained are that all hand sanitizers sampled have a diameter of inhibition as a strong antiseptic 10%, 50% sufficient and 40% weak.